2008
DOI: 10.1108/jopp-08-02-2008-b003
|View full text |Cite
|
Sign up to set email alerts
|

Procurement process maturity: key to performance measurement

Abstract: Performance measurement has been receiving increased attention in public organizations. As performance measurement systems begin to take on a central focus by public sector organizations, the challenges of measuring and improving critical organizational processes continue to increase in importance. Furthermore, as the procurement process continues to gain critical importance in public sector organizations, the need to apply specific performance measurement methods to measure and improve the procurement process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
19

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 2 publications
0
24
0
19
Order By: Relevance
“…In reviewing the literature in the public procurement field we decided to adopt this classification and add a fourth dimension, the process-related aspects of procurement design. We needed to add this process dimension because in the public sector the procurement process has the additional constraint of strict internal and external policy and regulation (Decarolis and Giorgiantonio, 2015) so the procurement process is an essential part of the overall organizational design (Rendon, 2008).…”
Section: Literature Review Of the Dimensions Of Procurement Departmenmentioning
confidence: 99%
“…In reviewing the literature in the public procurement field we decided to adopt this classification and add a fourth dimension, the process-related aspects of procurement design. We needed to add this process dimension because in the public sector the procurement process has the additional constraint of strict internal and external policy and regulation (Decarolis and Giorgiantonio, 2015) so the procurement process is an essential part of the overall organizational design (Rendon, 2008).…”
Section: Literature Review Of the Dimensions Of Procurement Departmenmentioning
confidence: 99%
“…Development can be effectively supported by government procurement [13][14][15]. On the other hand, from the perspective of empirical research, it is found that, as a financial expenditure, government procurement is conducive to improving the economic level of underdeveloped regions [16], which can improve the macro performance by driving overall economic growth, promoting employment and supporting enterprise development [17], and promoting independent regional innovation [18,19]. However, some scholars have questioned the economic benefits of government procurement, arguing that government procurement will hinder regional technological innovation [20] and reduce the capacity utilization rate of enterprises [21,22].…”
Section: Government Background Large Clients and Innovation Investmenmentioning
confidence: 99%
“…There is no much doubt that there has been growing interest in contract management in the developed world and hence the many studies of contracting and management (Rendon, 2008(Rendon, , 2009Abi-Karam, 2001;Okeahalam and Oludele, 2003;Davison and Wright, 2004;Minahan, 2007;Ya Ni and Bretschneider, 2007). Despite the emphasis and regulatory framework on contract management, Uganda Public Procurement Compliance Reports sanctioned by the Public Procurement and Disposal of Public Assets Authority have continuously shown contract management as one of the areas where performance of public entities is poor.…”
Section: The Research Problemmentioning
confidence: 99%